Charged Particles and Gamma-Ray Interaction with Gallium Barium Borate Glass: Theoretical Approach. Issue 1 (4th May 2022) - Limkitjaroenporn, P.; Insiripong, S.; Borisut, P.; Chaiphaksa, W.; Kaewkhao, J.; Sangwaranatee, N.
Abstract: The charged particle and gamma-ray shielding properties of gallium barium borate glass in composition (80-x)B2 O3 : xBaO: 20Ga2 O3 (where x  = 5, 10, 15, 20 and 25 mol%) were calculated and discuss in this work. The mass attenuation coefficient (μm ), the effective atomic number (Zeff ) and the effective electron density (Neff ) were calculated by using the WinXCom program in the energy range from 1 keV to 2 MeV. The results show the mass attenuation coefficients (μm ), the effective atomic number (Zeff ), and the effective electron density (Neff ) increase with increasing of BaO content reflected higher interaction probability at higher BaO composition in the glass matrix. The result of build-up factor are in the same trend and show the high value in the region which incoherent scattering is the main interaction. The mass stopping power and the projected range of proton and alpha particle have been simulate by SRIM program. The mass stopping power has maximum value at 0.9 MeV and 0.07 MeV for proton and alpha particles respectively. The projected range have the higher value at the higher kinetic energy of proton and alpha particle. Moreover the gallium barium borate glass system better have the proton and alpha shielding preperty when add barium oxide concentration due to weight fraction of barium increase in glass matrix.